Nepenthes ×taringkecil (Nepenthaceae), a new small-fanged nothospecies from West Kalimantan, Indonesia - Fadhil, Muhammad Hisyam; Irsyam, Arifin Surya Dwipa; Hariri, Muhammad Rifqi (Phytotaxa, 2026)
Nepenthes ×taringkecil is a newly described nothospecies from Mempawah Regency (West Kalimantan Province, Indonesia). This new nothospecies is a natural hybrid resulting from the cross between N. bicalcarata and N. mirabilis from which differs by canaliculate and sheathed petiole, non-swollen tendril, absence of tendril cavity, entire leaf margin, lower pitcher cylindrical in the upper half and globose in the lower half, fang-like peristome up to 6.6 mm long, orifice nearly horizontal at the apex and gradually curved at the base, and lid ovate to slightly reniform.